The relationship between task-technology fit and work perfomance among employees at Petronas Gas Berhad Transmission Operations Division Segamat Operations Centre / Nuriza Syazwani Mansor - Mansor, Nuriza Syazwani (Faculty of Business and Management, 2013)
The title of this study is "The Relationship between Task-Technology Fit and Work Performance among Employees at PETRONAS Gas Berhad Transmission Operations Division Segamat Operations Centre". The purpose of this research is to identify the relationship between the independent variables and dependent variables. Task-technology fit consists of 12 dimensions which consist of the right level of detail, accuracy compatibility,locatability, accessibility, meaning, assistance, ease of use of hardware and software, systems reliability, currency, presentation and confusion. For the dependent variable is about work performance. In order to conduct this research, the hypothesis is constructing to focusing on the objectives to identify the relationship between task-technology fit and work performance among employees in entitled organization. To gather data from this study, a set of questionnaire is distributed to employees who work at PETRONAS Gas Berhad Transmission Operations Division Segamat Operations Centre. There are 113 samples selected using a set of questionnaire consists of 57 types of questions, four for demographics section, 32 questions for tasktechnology fit section and 21 more questions for work performance section. Thus, data collected 85 questionnaires was returned back, further analysis is using reliability analysis, Pearson's correlation analysis for data analysis and Cronbach's alpha coefficient was used throughout this research study. Results show that there is a low correlation between task-technology fit and work performance.